PKM PENGUATAN KOMPETENSI PEDAGOGIK DAN LITERASI DIGITAL MAHASISWA MELALUI PENGEMBANGAN BUKU AJAR DAN MEDIA PEMBELAJARAN INOVATIF - Khasanah, Uswatun; Hadi, Imam Anas; Kustoro, Kustoro (Jurnal Indonesia Mengabdi, 2024)
This Community Partnership Program (PKM) aimed to strengthen students’ pedagogical competence and digital literacy through participatory training and practice-based mentoring in developing innovative textbooks and learning media. The program was conducted online on December 9, 2024, involving university students as the main participants. The implementation method consisted of four stages: preparation, core training, practice and mentoring, and evaluation and reflection. The results indicated an improvement in students’ understanding of systematic instructional design, their ability to develop structured digital textbooks, and their skills in creating interactive technology-based learning media. The participatory and practice-based approach proved effective in integrating pedagogical competence and digital literacy simultaneously. In addition to producing draft digital textbooks and innovative learning media, the program fostered reflective, collaborative, and adaptive mindsets among students as prospective 21st-century educators. Therefore, this training model can be recommended as an effective strategy for strengthening professional competencies of university students in teacher education programs.